2016
DOI: 10.1038/srep31313
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA-protein complexes: IMP3 protein component defines subfamily of circRNPs

Abstract: Circular RNAs (circRNAs) constitute a new class of noncoding RNAs in higher eukaryotes generated from pre-mRNAs by alternative splicing. Here we investigated in mammalian cells the association of circRNAs with proteins. Using glycerol gradient centrifugation, we characterized in cell lysates circRNA-protein complexes (circRNPs) of distinct sizes. By polysome-gradient fractionation we found no evidence for efficient translation of a set of abundant circRNAs in HeLa cells. To identify circRNPs with a specific pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
115
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(123 citation statements)
references
References 30 publications
(39 reference statements)
3
115
0
1
Order By: Relevance
“…In a recent study our group could provide biochemical evidence for distinct cytoplasmic circRNA-protein complexes in mammalian cells [28]. Since the anucleated platelets represent a very special system without active transcription, we analysed whether circRNAs in platelets are organised as circRNPs (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study our group could provide biochemical evidence for distinct cytoplasmic circRNA-protein complexes in mammalian cells [28]. Since the anucleated platelets represent a very special system without active transcription, we analysed whether circRNAs in platelets are organised as circRNPs (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Are we definitively convinced? It should be noted that this issue was recently also addressed in other studies, based on small subsets of abundant human circRNAs and polysome gradients [10,11], on global analysis of ribosomefootprinting data from human U2OS cells [12], and on polysome fractionation combined with RNA-seq in mouse brain [13]. These studies came to a negative answer and leave us with a controversial impression.…”
mentioning
confidence: 89%
“…Additionally, circFoxo3 was found to interact with CDK2 and p21 to repress cell cycle progression in cancer cell lines (27) and to promote cardiac senescence by interacting with ID-1, E2F1, FAK, and HIF1α in the mammalian heart (28) . Another study showed that a specific RBP, IGF2BP3, associates with several circRNAs (29) .…”
Section: Introductionmentioning
confidence: 99%